Risk Factors, Indications and Outcome of Emergency Obstetric Hysterectomy: A study performed at Tertiary Care Hospital - Lubna Aslam, Nudrat Sohail, Nazia Ayyub, Aiyza Sarwar, Azher Abbas Shah, Anam Afzal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Emergency obstetric hysterectomy is the life-saving surgical intervention when all other available measures are unable to control obstetric hemorrhage. In addition to the known indications and risk factors for globally increasing this near miss event, home deliveries by untrained birth attendants is irrefutable cause of obstetric morbidity and mortality Aim: To identify the risk factors and indications for EOH like Pakistan. Study design: Retrospective descriptive study. Settings: OB/GYN department of Lahore General Hospital, PGMI. Duration: Two years, from start of 2020 to the end of 2021. Methodology: All patients having emergency obstetric hysterectomy in Gynae Unit 3, were included in this study. Risk factors and indications for the procedure were recorded. Outcome in the form of morbidity and mortality was reviewed. Results: Out of total 6809 deliveries, 48 patients had EOH and majority were multiparous with age ranging from 20 to 35 years. Complicated home deliveries ending in EOH were 8.32% of the cases. Two third of the patients had one or more previous caesarean sections and 70.8% underwent Caesarean section in the index pregnancy. Most of the women, 81.25%, were un-booked cases. Most common indication for EOH (50%) in our study was uterine atony and 45.81% of the cases had morbidly adherent placenta. Conclusion: Rising trend of caesarian sections leading to placental issues, lack of proper antenatal care and deliveries at inappropriate places are the contributing factors in morbidity and mortality associated with EOH. Keywords: Uterine atony, morbidly adherent placenta, emergency obstetric hysterectomy.